The Role of Islam Religious Scholars in Politics - Syeda Dur e Nayab haider (Muslim Politics Review, 2025)
Usaama al-Azami’s Islam and the Arab Revolutions: The Ulama Between Democracy and Autocracy represents a significant contribution to the growing body of literature examining the political role of religious scholars in the modern Muslim world, particularly in the context of the Arab Spring. Published in 2022 by Oxford University Press, the book seeks to disturb centuries-old presumptions over the "apolitical" or "quietist" nature of most of these traditional ulama and instead lays bare how intimately involved they remain within broader systems of politics—either as the carriers of dissent or tools of authoritarian rule. Al-Azami’s work is distinguished not only by its bold argumentation but also by its nuanced methodology, combining textual analysis of sermons and public statements with broader theoretical reflections on Islamic authority, legitimacy, and political theology.